Effect of Walnut (Juglans regia) on Physico-chemical, Sensory and Storage Quality of Chevon Nuggets - Bhat, Asif Ahmad; Kumar, Arvind; Muzaffar, Zulhuma; Rather, Faroze Ahmad; Kaur, Manpreet (Journal of Meat Science, 2018)
The present study was undertaken to evaluate the possibl utilization of walnuts in the development of value added healthier chevon nuggets and to study their physico-chemical, sensory and storage properties. Four different levels of walnuts (Juglans regia) (0, 5, 10 and 15%) were selected to replace lean meat in the chevon nugget formulation. The chevon nuggets developed were analysed for various physicochemical and sensory parameters. Based on various parameters viz. physicochemical and sensory parameters a 10% level of wal nuts was adjudged as optimum for the preparation of walnut enriched chevon nuggets. Based on this study, chevon nuggets containing 10% levels of walnut was further studied for its storage quality. The optimized nuggets were aerobically packaged in low density poly ethylene pouches with density value of 0.930 g/cm3 along with control (0% levels of walnut) and evaluated for storage stability (physic ochemical, microbiological and sensory parameters) for 21 days under refrigerated condition (4±1oC). Both walnut enriched optimized nuggets and control were successfully stored for 7 days under refrigerated conditions (4±1oC) without marked loss in storage quality.